Coating layer for battery separator and manufacturing method thereof, battery separator and battery

By applying polymer coating materials containing polar functional groups on the lithium battery separation membrane, the deformation and wrinkle of the separation membrane during electrolyte injection is solved, the wetting and ionic conductivity of the battery are improved, and the battery performance is improved.

JP2025507495AInactive Publication Date: 2025-03-21SHENZHEN SENIOR TECH MATERIAL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024539653
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-07
Filing Date
2022-06-09
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing lithium battery separation membrane is prone to deform and shrink when electrolyte is injected, resulting in an increase in the internal dead space of the battery and affecting battery performance.

Method used

The coating material containing a dispersion medium, nanomaterial and polymer containing polar functional groups is used to improve the wettability and ionic conductivity of the separation membrane by controlling the surface pore size, roughness and hydroxyl content of the coating.

Benefits of technology

It effectively reduces the deformation and wrinkle of the separation membrane during electrolyte injection, improves the wettability and ionic conductivity of the battery, thereby improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025507495000001_ABST
    Figure 2025507495000001_ABST
Patent Text Reader

Abstract

A coating layer for a battery separator and its manufacturing method, a battery separator, and a battery, in which the coating layer for the battery separator includes a paste for the coating layer containing a dispersion medium, a nanomaterial, and a polar functional group-containing polymer, the coating layer has a surface pore size of 10-30 nm, a surface roughness of 200-500 nm, and a hydroxyl content in the coating layer of 100-4000 mg KOH / g. The coating layer for a battery separator and its manufacturing method, a battery separator, and a battery improve the problem of deformation of the battery separator caused by the electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of batteries, and more particularly to a coating layer for a battery separator and a method for making the same, a battery separator, and a battery. [Background technology]

[0002] Lithium battery separator is one of the main components of lithium ion battery, its performance has a very important impact on the overall performance of lithium battery, and is one of the key technologies that restrict the development of lithium battery. As the application field of lithium battery is constantly expanding and the impact of lithium battery products on people's lives is constantly becoming more and more serious, people's requirements for lithium battery performance are also increasing. In order to meet the development requirements of lithium battery, separator, as an important component of lithium battery, not only should have good chemical stability and low manufacturing cost, but also further improve the safety performance of lithium ion battery, which is the important trend of the current lithium battery development.

[0003] Currently, the separator used in lithium ion batteries is polyolefin, which has poor wettability with respect to the electrolyte. Therefore, when the electrolyte is injected into the semi-finished product after the battery is assembled, the electrolyte cannot spread quickly on the surface of the polyolefin separator. As a result, the separator is deformed and wrinkled due to the surface tension of the electrolyte, forming dead space inside the lithium battery, which affects the performance of the battery. Summary of the Invention [Problem to be solved by the invention]

[0004] The present invention provides a coating layer for a battery separator and a manufacturing method thereof, a battery separator and a battery, in order to improve the problem of deformation of the battery separator caused by an electrolyte. [Means for solving the problem]

[0005] According to a first aspect of the present invention, there is provided a coating layer for a battery separator, comprising: The above Coating Layer is formed from a coating paste, The paste includes a dispersion medium, a nanomaterial, and a polar functional group-containing polymer, and the coating layer has a surface pore size of 10-30 nm, a surface roughness of 200-500 nm, and a hydroxyl content in the coating layer of 100-4000 mg KOH / g.

[0006] In some embodiments, the dispersion medium and the nanomaterial form a dispersion liquid, and the content of the nanomaterial in the dispersion liquid is 0.1 to 30 wt % based on the mass of the dispersion medium.

[0007] In some embodiments, the nanomaterials are nanoparticles and one-dimensional nanomaterials. At least one of The particle size of the nanoparticle ceramic is smaller than 150 nm, preferably ≦100 nm; the length to diameter ratio of the one-dimensional nanomaterial is ≦50, and the length is ≦1000 nm.

[0008] In some embodiments, the nanomaterial comprises one or more of alumina, boehmite, magnesium hydroxide, magnesium oxide, barium sulfate, calcium carbonate, aluminum nitride, silicon carbide, hydroxyapatite, nanocellulose, attapulgite, aramid resin, polymethylmethacrylate, polyvinylidene fluoride, and polyethylene oxide.

[0009] In some embodiments, the polar functional group-containing polymer comprises polyacrylic acid, polyvinyl alcohol, carboxymethyl cellulose, or a composition thereof.

[0010] In some embodiments, the polar functional group-containing polymer is added in an amount of 1-30 wt % of the nanomaterial.

[0011] In some embodiments, the water content in the dispersion medium is 90 wt % or more.

[0012] According to a second aspect of the present invention, there is provided a method for producing a coating layer for a battery separator as described above, said method comprising the steps of: Intimately dispersing the nanomaterial in a dispersion medium to form a dispersion; adding a polar functional group-containing polymer to the dispersion to form a paste; Coating by adding etching agent or water eluting agent to the paste paste forming a According to the coating method, paste Coat the base film with The base film coated with the coating paste is drying to obtain a coated separator; The method includes a step of subjecting the coating separator to radiation treatment to cause an etching agent in the coating separator to react and generate gas, thereby etching the coating separator, and forming the coating layer having a rough surface, or a step of immersing the coating separator in water to cause a water-eluting agent in the coating separator to precipitate in the water, leaving depressions on the surface of the coating separator after elution, and forming the coating layer having a rough surface.

[0013] In some embodiments, the etchant comprises low molecular weight polyethylene, low molecular weight polypropylene, or a combination thereof.

[0014] In some embodiments, the low molecular weight polyethylene has a molecular weight less than 10,000 g / mol and the low molecular weight polypropylene has a molecular weight less than 10,000 g / mol.

[0015] In some embodiments, the radiation treatment comprises ultraviolet radiation or plasma radiation.

[0016] In some embodiments, the ultraviolet radiation has an ultraviolet light wavelength range of 100-300 nm, a power of 30-100 W / cm, and an irradiation time of 0.01-5 s.

[0017] In some embodiments, the base film is a polyolefin base film, the thickness of the base film is 3-30 microns, the drying temperature is 40-130° C., and the coating speed is 10-200 m / min.

[0018] In some embodiments, the water eluting agent is a polymeric nanoparticle, comprising polymethylmethacrylate, polyvinylidene fluoride, or a combination thereof, the polymeric nanoparticles have a diameter of 100-500 nm, and are used in an amount of 5-20 wt % of the nanomaterial.

[0019] In some embodiments, the coated separator is immersed in water for 1 to 5 minutes.

[0020] In some embodiments, the coating method includes at least one of spray coating, dip coating, microgravure roll coating, print coating, extrusion coating, and wire bar coating.

[0021] According to a third aspect of the present invention, there is provided a battery separator, the surface of which comprises the above-mentioned The phone The above-mentioned coating layer for the pond separator is also included. Made by The present invention relates to a coating layer for a battery separator, the coating layer being formed by the method.

[0022] The present invention 4 According to one aspect, the present invention provides a battery including a battery separator as described above. Effect of the Invention

[0023] In the coating layer for battery separator and its manufacturing method, the battery separator and the battery provided in the present invention, the number of hydroxyl functional groups in the coating layer, the surface pore size and the surface roughness are coordinated to jointly improve the wettability of the battery separator and increase the ion conduction efficiency. [Brief description of the drawings]

[0024] In order to more clearly describe the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces drawings that need to be used in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without making any creative efforts. [Figure 1] 1 is a flow chart of a method for making a coating layer for a battery separator in one embodiment. [Diagram 2] 4 is a flow chart of a method for making a coating layer for a battery separator in another embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0025] The technical solutions in the embodiments of the present invention are described below clearly and completely, and it is obvious that the described embodiments are only some of the embodiments of the present invention, and not all of the embodiments thereof. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without any creative efforts shall fall within the scope of protection of the present invention.

[0026] The inventors have found that coating the surface of a polyolefin separator with a ceramic material such as alumina or boehmite makes the ceramic material have excellent wettability to the electrolyte, thereby improving the wettability of the coated separator to the electrolyte. However, ceramic materials are generally on the order of microns or submicrons, and the pore diameters formed between the micron ceramic particles are on the order of microns, leaving large gaps on the surface that contacts the separator, while the electrolyte is transmitted along the ceramic surface, resulting in insufficient coverage of the micron-order pores, which results in areas of the micron-order pores that are not covered by the electrolyte, and thus forming dead spaces, which results in a reduction in the effective ion-conducting paths of the separator and a reduction in the ion-conducting speed. In order to reduce the effect of electrolyte injection on the deformation of the battery separator, the present invention provides a coating layer for the battery separator that has an affinity with the electrolyte.

[0027] The technical solutions of the present invention are described in detail below using specific embodiments. Some of the following specific embodiments can be combined with each other, and the same or similar concepts or processes may be omitted in some embodiments.

[0028] Particular embodiments of the present invention provide a coating layer for a battery separator, comprising: coatingThe paste comprises a dispersion medium, a nanomaterial and a polar functional group-containing polymer, the coating layer has a surface pore size of 10-30 nm, a surface roughness of 200-500 nm, and a hydroxyl content in the coating layer of 100-4000 mg KOH / g. The surface pore size of the coating layer may be any one or any two of 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm, 25 nm, 26 nm, 27 nm, 28 nm, 29 nm, 30 nm, the surface roughness may be 200 nm, 300 nm, 400 nm, 500 nm, the hydroxyl content in the coating layer may be any one or any two of 100 mg KOH / g, 500 mg KOH / g, 1000 mg KOH / g, 1500 mg KOH / g, 2000 mg KOH / g, 2500 mg KOH / g, 3000 mg KOH / g, 3500 mg KOH / g, 4000 mg KOH / g, and the selected coating paste of As the material changes, the corresponding values ​​can be selected and varied for testing.

[0029] The dispersion medium here may be any liquid that can be used to disperse materials, and the water content in the dispersion medium is 90 wt % or more, and the dispersion medium may further contain a dispersion medium such as ethanol, acetone, N-methylpyrrolidone, etc.

[0030] Here, the dispersion medium and nanomaterial form a dispersion liquid, and the content of the nanomaterial in the dispersion liquid is 0.1 to 30 wt%, based on the mass of the dispersion medium. For example, the content may be any one or a range between any two of 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, and 30 wt%. In some embodiments, the nanomaterials are nanoparticles and one-dimensional nanomaterials. At least one of The particle size of the nanoparticle ceramic is smaller than 150 nm, preferably ≦100 nm; the length to diameter ratio of the one-dimensional nanomaterial is ≦50, and the length is ≦1000 nm.

[0031] Here, the nanomaterials include one or more of alumina, boehmite, magnesium hydroxide, magnesium oxide, barium sulfate, calcium carbonate, aluminum nitride, silicon carbide, hydroxyapatite, nanocellulose, attapulgite, aramid resin, polymethyl methacrylate, polyvinylidene fluoride, and polyethylene oxide.

[0032] The polar functional group-containing polymer may comprise polyacrylic acid, polyvinyl alcohol, carboxymethyl cellulose, or a composition thereof. In some embodiments, the polar functional group-containing polymer is added in an amount of 1-30 wt% of the nanomaterial mass, such as any one or any two of 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt%, 16 wt%, 17 wt%, 18 wt%, 19 wt%, 20 wt%, 21 wt%, 22 wt%, 23 wt%, 24 wt%, 25 wt%, 26 wt%, 27 wt%, 28 wt%, 29 wt%, and 30 wt%.

[0033] Based on research into the coating layer, the inventors have found that a smaller pore size of the coating layer can effectively reduce the size of the gap at the contact surface between the nanomaterial coating layer and the separator, thereby solving the problem of the existence of dead space; a smaller surface pore size of the coating layer increases the resistance to the electrolyte penetration, so it is necessary to increase the polar groups to ensure its wettability; however, if the hydroxyl content is too high, the electrolyte will form a dense liquid film and will not be able to penetrate the coating layer, so there is a mutually coordinated relationship between the pore size of the coating layer and the number of polar groups. The coating layer provided in this application has a certain number of hydroxyls to ensure affinity for the electrolyte; And the coating layer The nano-order pores play a capillary role and can ensure that the electrolyte is adsorbed. The combination of a certain number of hydroxyls, nano-order pores and a certain degree of roughness can ensure that the electrolyte has good diffusivity and is adsorbed to the maximum extent, thereby mitigating the impact of the electrolyte on the separator. The present application combines the pore size, surface roughness and hydroxyl content of the coating layer to jointly improve the wettability of the separator and improve the ion conduction efficiency.

[0034] To obtain the coating layer for the battery separator, an embodiment of the present invention uses the above-mentioned The phone There is further provided a method for producing a coating layer for a battery separator.

[0035] Referring to FIG. 1, in one embodiment, a method for manufacturing a coating layer for a battery separator includes the following steps S1 to S5.

[0036] S1, in dispersing nanomaterials, the nanomaterials are thoroughly dispersed in a dispersion medium to form a dispersion liquid. The dispersion medium may be any liquid that can be used to disperse materials, and the water content in the dispersion medium is 90 wt% or more, and may further contain a dispersion medium such as ethanol, acetone, or N-methylpyrrolidone. Dispersion methods include high-speed stirring, high-pressure homogenization, and sand mill dispersion. Nanomaterials as a dispersion medium The content of the nanomaterial in the dispersion liquid may be 0.1 to 30 wt%, and the nanomaterial may be a nanoparticle or a one-dimensional nanomaterial. At least one of wherein the particle size of the nanoparticles is less than 150 nm, the length to diameter ratio of the one-dimensional nanomaterial is ≦50, and the length is ≦1000 nm.

[0037] S2: In the introduction of polymer, a polar functional group-containing polymer such as polyacrylic acid, polyvinyl alcohol, or carboxymethyl cellulose is added to the dispersion in an amount of 1 to 30 wt% of the mass of the nanomaterial. to form a paste .

[0038] S3, in the addition of etching agent, paste Add an etching agent to to form a coating paste. The etching agent includes low molecular weight polyethylene, low molecular weight polypropylene, or a composition thereof, where the molecular weight of the low molecular weight polyethylene or low molecular weight polypropylene is less than 10,000 g / mol.

[0039] S4, in the case of film formation by coating, produced by the coating method Coating Paste is coated on the base film and dried to obtain a coated separator. The coating method is spray coating, dip coating, microgravure roll coating, print coating, extrusion coating, wire bar coating, etc., but it goes without saying that other conventional coating methods may be selected. The base film is a polyolefin base film, the thickness is 3-30 microns, the drying temperature is 40-130°C, and the coating speed is 10-200m / min.

[0040] In S5, etching, the coating separator is irradiated with radiation to react with an etchant and generate gas, thereby etching the coating separator and forming the coating layer having a rough surface. The radiation treatment may be treatment using means such as ultraviolet radiation or plasma radiation. The wavelength range of the ultraviolet radiation is 100-300 nm, the power is 30-100 W / cm, and the irradiation time is 0.01-5 s.

[0041] Referring to FIG. 2, in another specific embodiment, the present invention further provides a method for preparing a coating layer for another battery separator, the method including the following steps S1 to S5.

[0042] S1, in dispersing a nanomaterial, the nanomaterial is sufficiently dispersed in a dispersion medium to form a dispersion liquid. The dispersion medium may be any liquid that can be used to disperse materials, and the water content in the dispersion medium is 90 wt% or more, and the dispersion medium may further contain a dispersion medium such as ethanol, acetone, or N-methylpyrrolidone. As a dispersion method, the nanomaterial is uniformly dispersed in the dispersant using a method such as high-speed stirring, high-pressure homogenization, or sand mill dispersion. The content of the nanomaterial in the dispersion liquid may be 0.1 to 30 wt%, and the nanomaterial is a nanoparticle or a one-dimensional nanomaterial. At least one of wherein the particle size of the nanoparticles is less than 150 nm, the length to diameter ratio of the one-dimensional nanomaterial is ≦50, and the length is ≦1000 nm.

[0043] S2: In the introduction of polymer, a polar functional group-containing polymer such as polyacrylic acid, polyvinyl alcohol, or carboxymethyl cellulose is added to the dispersion in an amount of 1 to 30 wt% of the mass of the nanomaterial. to form a paste .

[0044] S3, in the addition of water eluent, paste Add water eluent to to form a coating paste.The water eluent has a low affinity with the ceramic particles, and the water eluent is preferentially eluted in water, leaving depressions on the surface of the coated separator after elution, forming the coating layer with a rough surface. In some embodiments, the water eluent can be selected from polymer nanoparticles such as polymethyl methacrylate, polyvinylidene fluoride, or a composition thereof, the diameter of the nanoparticles is 100-500 nm, and the amount used is about 100-200 μm. particle The weight of the material is 5 to 20 wt%.

[0045] S4, in the case of film formation by coating, produced by the coating method Coating Paste is coated on the base film and dried to obtain a coated separator. The coating method is spray coating, dip coating, microgravure roll coating, print coating, extrusion coating, wire bar coating, etc., but it goes without saying that other conventional coating methods may be selected. The base film is a polyolefin base film, the thickness is 3-30 microns, the drying temperature is 40-130°C, and the coating speed is 10-200m / min.

[0046] In S5, water dissolution, the coated separator is immersed in water to cause the water-eluting agent in the coated separator to precipitate in the water, leaving depressions on the surface of the coated separator after dissolution, thereby forming the coating layer having a rough surface. The time for immersing the coated separator in water is 1 to 5 minutes.

[0047] The performance of the products of some examples of the present invention and comparative examples will be analyzed through experiments below.

[0048] With reference to Table 1, the separators of Examples 1 to 8 and Comparative Examples 1 to 10 in Table 1 were produced and their performance tested in the following manner.

[0049] 1. Membrane production Regarding the base membrane, the base membrane used in Examples 1 to 8 and Comparative Examples 1 to 10 is a polyethylene membrane having a thickness of 5 microns, a porosity of 40%, and a pore size of 40 nm. Regarding the separator, the separator is manufactured by the etching method of Fig. 1, and the etching method specifically includes the following steps S1 to S5.

[0050] S1, Dispersion of nanomaterials: Nanomaterials were thoroughly dispersed in a dispersion medium to form a dispersion liquid. The dispersion medium was water.

[0051] In S2, introduction of polymer, a polar functional group-containing polymer was added to the above dispersion to form a paste.

[0052] S3, in the addition of etching agent, paste Coating with added etching agent paste was formed.

[0053] S4, in the case of film formation by coating, produced by the coating method Coating Paste was coated onto the base film and dried to obtain a coated separator.

[0054] In S5, in the etching step, the coating separator is irradiated with ultraviolet radiation to cause an etching agent to react and generate gas, thereby etching the coating separator and forming the coating layer having a rough surface.

[0055] Here, specific manufacturing parameters for each of the examples and comparative examples are shown in Table 1.

[0056] 2. Electrolyte absorption rate test 1. Test method for the liquid absorption rate of the base film: (1) 150mm x 150mm (S = 0.0225m 2 ) of size Base membrane(2) Cut out a sample of the sample, weigh the sample, and record the mass m1; (3) Immerse the sample in the electrolyte (EC:EMC=7:3vol%, LiFP6 1mol) for 1h; (4) Place a clean tissue paper (area larger than 150mm x 150mm) flat on a flat table, take out the sample, place it on the tissue paper, and wipe it with another clean tissue paper. Base membrane (4) After wiping the sample dry, the free electrolyte on the surface of the sample is lightly wiped off, and then wiped with another clean tissue paper until the particulate electrolyte is no longer visible to the naked eye. The sample is then weighed (mass m2) and the liquid absorption rate (unit: g / m2) is calculated. 2 ) The area liquid absorption rate = (m2-m1) / S was calculated.

[0057] 2. Regarding the test method for the electrolyte absorption rate of the coating layer, the electrolyte absorption rate of the coating layer can be obtained by testing the electrolyte absorption rates of the base membrane and the composite separator (base membrane with coating layer) separately using method 1 and subtracting the two.

[0058] 3. Diffusion rate of electrolyte on the membrane surface (1) Place a glass slide under an optical microscope, cut out a 50mm x 50mm separator sample, mark the MD / TD directions, and attach the sample to the glass slide with tape. (2) 2 μL of electrolyte (EC:EMC=7:3 vol%, LiFP6 1 mol) was dropped onto the fixed sample, and at the same time, a timer was pressed. When the droplet stopped spreading, the spreading time t (s) was recorded, and the morphology of the spread droplet was recorded using an optical microscope. (3) Using computer analysis software, the hydraulic radius R (mm) of the dispersed droplet is calculated, and the spreading velocity V (mm / s) is calculated based on the equation V = R / t. (4) The above experiment was repeated three times, and the average diffusion rate was calculated.

[0059] 4. Parameter measurement and evaluation The detection method for hydroxyl content was based on GB / T 12008.3-2009.

[0060] The pore size of the surface layer was examined by high-resolution scanning electron microscopy.

[0061] The surface roughness was tested by a 3D profilometer.

[0062] How to evaluate the degree of deformation, and what is meant by no deformation, deformation, large deformation, and serious deformation? A wrinkle evaluation test using liquid injection is performed. The separator, positive electrode, and negative electrode are assembled into a battery, and then electrolyte is injected. After leaving it for a certain period of time, the battery is disassembled and the deformation status of the separator is checked. If no wrinkles are observed, it is considered to be no deformation. If wrinkles are observed and the number of wrinkles is less than 3, it is considered to be deformed. If the number of wrinkles is more than 3 but less than 10, it is considered to be large deformation, and if the number of wrinkles is more than 10, it is considered to be large deformation. If it is more than , serious deformation.

[0063] 5. Test results and analysis The data obtained from the test are shown in Table 1. and Table 2 As shown in. [Table 1-1] [Table 1-2] [Table 2]

[0064] As can be seen from the comparison of Examples 1-4 and Comparative Examples 1-2, when the content of -OH increases, the diffusion speed of the electrolyte solution gradually increases and then remains unchanged. The reason for this phenomenon is that the increase in -OH contributes to the diffusion of the electrolyte solution on the surface, but if it is too much, the electrolyte solution speed reaches its limit. When the content of -OH is 50 mg KOH / g, the separator is deformed, but when the content of -OH is increased to 100 mg KOH / g, the separator does not deform any more, and in the range of 100 to 4000 mg KOH / g, no further deformation is observed, but when the content of -OH is further increased to 4500 mg KOH / g, the coated separator begins to deform. The reason for this phenomenon is that when the content of hydroxyl is lower than 100 mg KOH / g, the wettability of the coating layer to the electrolyte solution is insufficient, so the absorption rate of the coated separator to the electrolyte solution is reduced and the separator is deformed. When the hydroxyl content is greater than 4000 mg KOH / g, the coating layer has a very high adsorption property for the electrolyte, which causes a dense liquid membrane of the electrolyte to form on the surface of the coating layer, preventing the electrolyte from smoothly entering the pores of the coating layer. As a result, the electrolyte accumulates on the surface of the separator, reducing the electrolyte absorption rate of the coated separator (the electrolyte absorption rate of the coated separator is reduced in Example 4 and Comparative Example 2), causing deformation of the separator. If the surface roughness becomes even greater and the electrolyte accumulates and increases on the membrane surface, the excess electrolyte will Coating separator As a result, the impact on the coating Serious deformation of the separator was observed.

[0065] As can be seen from Examples 5-6 and Comparative Examples 4-5, when the pore diameter of the surface layer is smaller than 10 nm or larger than 30 nm, the separator is deformed by the injection of the electrolyte, but when the diameter is within the range of 10-30 nm, the shape of the separator does not change. This is mainly because when the pore diameter is too small, the resistance to the electrolyte entering the coating layer increases, but when the diameter is 10-30 nm, the capillary action is strong. If the pore diameter continues to increase, the capillary action decreases, and the electrolyte cannot be sufficiently absorbed.

[0066] As can be seen from Examples 2 and 8 and Comparative Examples 6 to 8, when the roughness is 300 nm or 500 nm, the coated separator has excellent resistance to deformation caused by the electrolyte, but when the roughness is 100 nm, 800 nm, or 1000 nm, the characteristics are all poor. The main reason for this phenomenon is that when the roughness is too small, the electrolyte absorption area is limited, The coating layer On the other hand, if the roughness is too large, the high defect difference suppresses the transmission and dispersion of the electrolyte, and the electrolyte cannot diffuse sufficiently to the surroundings, so it accumulates on the surface of the membrane in a liquid form.

[0067] The present application is designed to ensure that the coating layer has a certain number of hydroxyls and has affinity for the electrolyte, and the nano-order pores act as capillaries to allow the electrolyte to flow through the coating layer. In the coating layer In addition, a certain degree of roughness can ensure that the electrolyte is adsorbed. In the coating layer It can ensure maximum adsorption and transport, thereby mitigating the impact of the electrolyte on the separator. The pore size, surface roughness and hydroxyl content of the coating layer are coordinated to improve the wettability of the separator and increase the ion conduction efficiency.

[0068] An embodiment of the present invention further provides a battery separator, the battery separator being manufactured using the above-referenced manufacturing method.

[0069] An embodiment of the present invention further provides a battery including a battery separator according to the above alternative solution.

[0070] In the description herein, the use of terms such as "one embodiment," "one example," "particular implementation," "one example," and the like means that the specific features, structures, materials, or characteristics described with reference to that example or example are included in at least one example or example of the present invention. In the present specification, exemplary expressions of the above terms do not necessarily refer to the same example or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more examples or examples.

[0071] Finally, the above embodiments are only used to describe the technical solutions of the present invention, and are not intended to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art may still modify the technical solutions described in the above embodiments, or make equivalent substitutions for part or all of the technical features thereof, and such modifications or substitutions do not cause the essence of the corresponding technical solutions to depart from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A coating layer for a battery separator, characterized in that the paste of the coating layer comprises a dispersion medium, a nanomaterial and a polar functional group-containing polymer, the coating layer has a surface pore size of 10-30 nm, a surface roughness of 200-500 nm, and a hydroxyl content in the coating layer of 100-4000 mg KOH / g.

2. The coating layer for a battery separator as described in claim 1, characterized in that the dispersion medium and the nano material form a dispersion liquid, and the content of the nano material in the dispersion liquid is 0.1 to 30 wt %, based on the mass of the dispersion liquid.

3. 2. The coating layer for a battery separator as described in claim 1, characterized in that the nanomaterials include nanoparticles and one-dimensional nanomaterials, the particle diameter of the nanoparticles is smaller than 150 nm, the length-to-diameter ratio of the one-dimensional nanomaterial is ≦50, and the length is ≦1000 nm.

4. 4. The coating layer for battery separator according to claim 1, wherein the nano-material comprises one or more of alumina, boehmite, magnesium hydroxide, magnesium oxide, barium sulfate, calcium carbonate, aluminum nitride, silicon carbide, hydroxyapatite, nanocellulose, attapulgite, aramid resin, polymethylmethacrylate, polyvinylidene fluoride, and polyethylene oxide.

5. 2. The coating layer for battery separator according to claim 1, wherein the polar functional group-containing polymer comprises polyacrylic acid, polyvinyl alcohol, carboxymethyl cellulose, or a composition thereof.

6. 2. The coating layer for battery separator as claimed in claim 1, wherein the polar functional group-containing polymer is added in an amount of 1-30 wt % of the nanomaterial.

7. 2. The coating layer for a battery separator as claimed in claim 1, wherein the water content in the dispersion medium is 90 wt % or more.

8. A method for producing a coating layer for a battery separator according to any one of claims 1 to 7, comprising the steps of: Intimately dispersing the nanomaterial in a dispersion medium to form a dispersion; adding a polar functional group-containing polymer to the dispersion to form a paste; adding an etching agent or a water-eluting agent to the paste to form a coating liquid; Coating the coating solution on a base membrane by a coating method, and drying to obtain a coating separator; a step of subjecting the coating separator to radiation treatment to cause an etching agent in the coating separator to react and generate gas, thereby etching the coating separator and forming the coating layer having a rough surface, or a step of immersing the coating separator in water to cause a water-eluting agent in the coating separator to precipitate in the water, leaving a depression on the surface of the coating separator after elution, thereby forming the coating layer having a rough surface.

9. 9. The method for preparing a coating layer for a battery separator as claimed in claim 8, wherein the etching agent comprises low molecular weight polyethylene, low molecular weight polypropylene, or a composition thereof.

10. 10. The method for preparing a coating layer for a battery separator as claimed in claim 9, wherein the molecular weight of the low molecular weight polyethylene is lower than 10,000 g / mol, and the molecular weight of the low molecular weight polypropylene is lower than 10,000 g / mol.

11. 9. The method for preparing a coating layer for a battery separator according to claim 8, characterized in that the radiation treatment comprises ultraviolet radiation or plasma radiation, wherein the ultraviolet light of the ultraviolet radiation has a wavelength range of 100-300 nm, a power of 30-100 W / cm, and an irradiation time of 0.01-5 s.

12. 9. The method for producing a coating layer for a battery separator according to claim 8, characterized in that the base film is a polyolefin base film, the thickness of the base film is 3-30 microns, the drying temperature is 40-130°C, and the coating speed is 10-200 m / min.

13. 9. The method for producing a coating layer for a battery separator according to claim 8, characterized in that the water-eluting agent is a polymer nanoparticle, comprising polymethyl methacrylate, polyvinylidene fluoride or a composition thereof, the diameter of the polymer nanoparticle is 100-500 nm, and the amount of the nanoparticle used is 5-20 wt % of the nanoparticle.

14. 9. The method for manufacturing a coating layer for a battery separator according to claim 8, wherein the time for immersing the coated separator in water is 1 to 5 minutes, and the coating method includes at least one of spray coating, dip coating, microgravure roll coating, print coating, extrusion coating, and wire bar coating.

15. A battery separator, characterized in that the surface thereof has a coating layer for a battery separator according to any one of claims 1 to 7, or has a coating layer for a battery separator manufactured by the manufacturing method according to any one of claims 8 to 14.

16. 16. A battery comprising the battery separator of claim 15.

Citation Information

Patent Citations

  • Polyethylene micropore diaphragm containing organic / inorganic composite cross-linking coating and preparation method of polyethylene micropore diaphragm

    CN104701479A

  • Porous lithium ion battery diaphragm, preparation method and lithium ion battery

    CN114039167A

  • Electrode assembly and secondary battery having the same

    JP2009238752A